2017
DOI: 10.3238/arztebl.2017.0581
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Strain as a Risk for Hip Osteoarthritis

Abstract: The studies are moderately to highly heterogeneous. An association exists between years of lifting heavy loads or other kinds of physical strain on the job and the risk of developing osteoarthritis of the hip. The greater the exposure, the greater the risk. The evidence base for risk assessment in women is currently inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 39 publications
1
36
1
4
Order By: Relevance
“…For all studies (except for the small study of [ 7 ] with only two exposure categories) we assigned the highest exposure category among men at approximately the 90th exposure percentile (range of percentiles of the highest exposure category: 82.1st to 91.2nd; median: 90.2nd percentile). The previous pooled analysis (see [ 2 ]) found that the highest exposure categories of the studies included approximately doubled the risk among men (OR 2.09; 95% CI 1.4–3.1). Therefore, the doubling dose should correspond to approximately the 90th percentile of the cumulative exposure values of the reference population.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For all studies (except for the small study of [ 7 ] with only two exposure categories) we assigned the highest exposure category among men at approximately the 90th exposure percentile (range of percentiles of the highest exposure category: 82.1st to 91.2nd; median: 90.2nd percentile). The previous pooled analysis (see [ 2 ]) found that the highest exposure categories of the studies included approximately doubled the risk among men (OR 2.09; 95% CI 1.4–3.1). Therefore, the doubling dose should correspond to approximately the 90th percentile of the cumulative exposure values of the reference population.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-regression analysis was based on our recently published systematic review [ 2 ] on the relationship between physical workload and osteoarthritis of the hip. We first performed an update (until March 31, 2017) of our literature search using the published search strategy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations